2012
DOI: 10.4236/jep.2012.31006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Leakage Pollution of Longpan Road Gas Station and Its Enlightenment

Abstract: Geological penetrating radar combined with drilling and chemical analysis has been applied to investigate leakage pollution of Longpan Road gas station in Nanjing, China. The results indicate that radar images show strong reflection anomalies along the northeast to the gas station, characterized by contaminants or contaminant plumes spreading downstream and below. The drilling results confirmed the contents of monocyclic and polycyclic aromatic hydrocarbons contained in the layers of fine sands ranging from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Shell' investigation found that over 1,100 gas stations leaking oil had lead to severe soil and underground water pollution in the UK. Similar pollution in the Czech Republic, Hungary, the former Soviet Union and South America had also been reported 1 .…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Shell' investigation found that over 1,100 gas stations leaking oil had lead to severe soil and underground water pollution in the UK. Similar pollution in the Czech Republic, Hungary, the former Soviet Union and South America had also been reported 1 .…”
Section: Introductionsupporting
confidence: 80%
“…Comparing with other industry wastewater discharge, the pollution of soil and underground water by gas station leaking or leakage from underground soil tanks is more difficult to determine, if these happen, it will lead to grave consequence 1 . The US EPA took an investigation about the underground tanks built before September 2001, it indicated that there are 420,000 leaking tanks and nearly 150,000 of which need remediation 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These features correspond to a hydrocarbon vapor phase in the vadose zone, or the region between the surface and the water table, in which the pores in the rock are not filled completely with water, as described by Castro and Branco (2003). A number of other studies have also applied GPR to investigate the contamination of the subsurface by leaked fuel, recording contaminant plumes at depths of up to approximately 4 m (e.g., Srigutomo et al 2016;Subba Rao e Chandrashekhar 2014;Jiang et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…We acquired GPR data to detect possible contamination plumes caused by hydrocarbons in the subsurface of the study area. Many previous studies have shown that GPR is an adequate geophysical tool for the detection of contaminated environments (e.g., Bacha et al 2021;Aktürk and Doyuran 2015;Jiang et al 2012;Castro and Branco 2003;Atekwana et al 2000).…”
Section: Ground Penetrating Radar (Gpr)mentioning
confidence: 99%
“…Indeed, in previous years, other authors [8,18,31,32] have exploited GPR practicality in outlining contamination areas due to solid waste pollution giving back results in terms of reflection anomalies correlated to the presence of contaminant spreading.…”
Section: Introductionmentioning
confidence: 99%